The forgotten fire - Bagdasarian, Adam (DK Pub., 2000)
In 1915 Vahan Kenderian is living a life of privilege as the youngest son of a wealthy Armenian family in Turkey. This secure world is shattered when some family members are whisked away while others are murdered before his eyes. Vahan loses his home and family, and is forced to live a life he would never have dreamed of in order to survive. Somehow Vahan<U+2019>s incredible strength and spirit help him endure, even knowing that each day could be his last.